'With divided mind and unsure steps': South Africa from referendum to republic, August 1960 May 1961 - Bron-Swart, Eleanor Janet (University of the Free State, 2021)
In October 1960 the South African government held a Whites-only referendum on whether South Africa should become a republic. The establishment of the republic is often seen as the 'last battle of the Boer War' and therefore interpreted as a political matter with Afrikaners in opposition to English-speaking South Africans. The referendum question did not solely affect South Africa's constitutional structure. Numerous voters and politicians were concerned that South Africa would be excluded from the Commonwealth and would become increasingly isolated due to the apartheid policy upon becoming a republic. After gaining a narrow majority in favour of a republic, the government withdrew South Africa from the Commonwealth in March 1961 and proceeded with the establishment of the republic in May of that same year. Despite the 52% vs 48% outcome of the referendum, the period is often seen as a period of increasing unity between white political groupings. The lack of opposition from white citizens to this process is frequently interpreted as a sign of increased support for the National Party. This thesis explores the events and motivations from the referendum to the republic as a complex political issue by examining public opinion and voter motivation. The primary sources used in this thesis are editorials and readers' letters published in mainstream newspapers. Readers' letters and editorials were examined at three intervals: during the referendum campaigns, in reaction to the withdrawal from the Commonwealth, and at the establishment of a republic which coincided with anti-apartheid demonstrations. These opinions were analysed qualitatively and quantitatively in conjunction with archival source material. This thesis utilises an in-depth analysis of white public opinion to explore the factors that politically motivated the white electorate in their acceptance or rejection of a republic. The thesis argues that the economy and racial politics were decisive factors in determining the outcome of the referendum and the reactions to the events that followed. The establishment of the republic is often seen as part of the National Party's road to political domination and as being driven by white cultural-political divisions. Close analysis of public opinion highlights how this process was, however, one of 'divided mind and unsure step' for numerous members of the white electorate.
Thesis (Ph.D. (Centre for Africa Studies))--University of the Free State, 2021
Keywords: South Africa; Republic; Referendum; Commonwealth; National Party; United Party; United Party; English-speaking South Africans; Newspapers; Public Opinion